Adolescents' experiences of being food-hypersensitive: a qualitative study - Wilde-Larsson Bodil; Marklund Birgitta; Ahlstedt Staffan; Nordström Gun (BMC, 2007)
Abstract Background Experiencing or being at risk of adverse reactions to certain food items is a common health issue, especially among children and adolescents. Research has shown that living with the risk of food reactions and always having to take measures to avoid certain food in one's diet has a negative impact on quality of life. The aim of this study was to illuminate adolescents' experiences of being food hypersensitive. Methods Three focus group interviews and six individual interviews were carried out with all together 17 adolescents, 14-18 years of age, who had exclusion diets at school due to food hypersensitivity. The interviews were taped and transcribed verbatim and a qualitative content analysis was carried out. Results Five categories with subcategories, and one pervading theme, emerged. The categories were: Perceiving oneself as being particular, Feeling constrained, Experiencing others' ignorance, Keeping control, and Feeling it's okay. A pervading theme was conceptualised as Striving to normalise the experience of being food-hypersensitive. The adolescents regarded themselves as competent and courageous, but also described how they avoided the extra attention it implied to ask for special food considerations taken into account. Their self-conceptions were probably essential for their management of and attitude toward the hypersensitivity condition. They felt deprived, and those at risk of severe food reactions experienced insecurity and fear. Feelings of being disregarded were expressed, as well as facing unreliability and a lack of understanding from others. The continual work of constant vigilance and decision-making was described as time-consuming and frustrating. However, the adolescents also experienced considerate and supportive surroundings and were at pains to tone down the negative experiences and consequences of being food-hypersensitive. Conclusion Food avoidance by itself, and not only the somatic food reactions, brings about consequences with significant impacts on adolescents' lives. The findings from this study have implications for all of those who deal with adolescents who are food-hypersensitive, and not only health professionals. A deeper insight into adolescents' experiences gives an understanding which can improve the care-givers' efforts.